Silica Aerogel-Polycaprolactone Scaffolds for Bone Tissue Engineering - Pontinha, Ana (2023)
Silica aerogel is a material composed of SiO2 that has exceptional physical properties when utilized for tissue engineering applications. Poly-ε-caprolactone (PCL) is a biodegradable polyester that has been widely used for biomedical applications, namely as sutures, drug carriers, and implantable scaffolds. Herein, a hybrid composite of silica aerogel, prepared with two different silica precursors, tetraethoxysilane (TEOS) or methyltrimethoxysilane (MTMS), and PCL was synthesized to fulfil bone regeneration requirements. The developed porous hybrid biocomposite scaffolds were extensively characterized, regarding their physical, morphological, and mechanical features. The results showed that their properties were relevant, leading to composites with different properties. The water absorption capacity and mass loss were evaluated as well as the influence of the different hybrid scaffolds on osteoblasts’ viability and morphology. Both hybrid scaffolds showed a hydrophobic character (with water contact angles higher than 90°), low swelling (maximum of 14%), and low mass loss (1–7%). hOB cells exposed to the different silica aerogel-PCL scaffolds remained highly viable, even for long periods of incubation (7 days). Considering the obtained results, the produced hybrid scaffolds may be good candidates for future application in bone tissue engineering.